A self-activating nanovesicle with oxygen-depleting capability for efficient hypoxia-responsive chemo-thermo cancer therapy. (February 2021) - Chen, Shi-Xiong; Xue, Fengfeng; Kuang, Yichen; Chen, Siyu; Sheng, Danli; Chen, Hangrong
Abstract: Hypoxia-activated prodrugs (HAPs) promise to mitigate side effects of conventional chemotherapy and to enable precise medication treatment. One challenge facing HAPs-based chemotherapy is prodrug failure in normoxic tumor region. However, current strategies to enhance tumor hypoxia rely on delivery of oxygen-consuming agents and external stimulation, which can impede the optimal application of HAPs. Herein, a novel self-activating nanovesicle, TH-302@BR-Chitosan NPs, is constructed by assembling bilirubin-chitosan conjugate (named as BR-Chitosan) with a HAP, TH-302. It is interesting to find that the BR-Chitosan shows the inherent oxygen-depleting performance, especially in the presence of over expressed H2 O2 in tumor area, during which the BR-Chitosan can facily transform into biliverdin-chitosan (BV-Chitosan) and subsequently result in the disassembly of nanovesicles to release and activate the prodrug. Thus, this in situ strengthening hypoxia level of tumor can greatly promote the chemotherapy efficacy of HAPs. Moreover, as the oxidation derivatives of BR-Chitosan, BV-Chitosan exhibits intense absorbance at the range from long wavelength of visible region to near-infrared region, which can be acted as an effective photothermal agent for photothermal therapy (PTT). This biodegradable and self-activating nanovesicle with concise formulation demonstrates greatly enhanced synergistic therapeutic outcome in the activatable chemo-thermo combined therapy, showing much promising in future clinical transformation. Graphical abstract: A self-activating nanovesicle with inherent oxygen-depleting capability is developed by assembling bilirubin-chitosan conjugate with a model hypoxia-activated prodrug (TH-302). This BR-Chitosan-based nanovesicle can greatly consume oxygen in H2O2-rich tumor area to enhance therapeutic outcome of TH-302 and realize activatable photothermal conversion for combined chemo-thermo therapy, providing a novel strategy for hypoxia-based cancer treatment. Image 1 Highlights: Bilirubin-chitosan conjugate shows inherent oxygen-depleting capability. Fabricate a responsive bilirubin-based nanovesicle for enhanced hypoxia-based chemotherapy. The biliverdin-chitosan derived from bilirubin-chitosan exhibits photothermal effect. Achieve synergistic outcome of oxidation-activatable PTT and hypoxia-based chemotherapy.